2014
DOI: 10.1038/onc.2014.22
|View full text |Cite|
|
Sign up to set email alerts
|

MMP7-mediated cleavage of nucleolin at Asp255 induces MMP9 expression to promote tumor malignancy

Abstract: Nucleolin (NCL) participates in DNA transcription, ribosomal biogenesis and the regulation of RNA stability. However, the contribution of NCL to tumor development is still not clear. Herein, we found that NCL expression correlated with poor prognosis in lung cancer patients. Overexpressed NCL was predominantly cleaved to C-terminal truncated NCL (TNCL). In lung cancer formation, activation of the epidermal growth factor receptor pathway induced NCL expression, and also the expression of matrix metalloproteinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
4
22
1
Order By: Relevance
“…MMP‐7 and MMP‐9 can be activated by downstream transcription factors such as β‐catenin, c‐JUN, PEA3, EGF and LEF‐1 . The most recent study indicated that MMP7 can not only cleave the extracellular matrix (ECM) to promote tumor invasion but also cleaves nucleolin to stabilize MMP9 expression in order to augment oncogenesis . Furthermore, the combined expression of MMP7 and MMP9 has been suggested to be a good marker for the degree of malignancy and for the presence of lymphatic metastasis in esophageal cancer .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP‐7 and MMP‐9 can be activated by downstream transcription factors such as β‐catenin, c‐JUN, PEA3, EGF and LEF‐1 . The most recent study indicated that MMP7 can not only cleave the extracellular matrix (ECM) to promote tumor invasion but also cleaves nucleolin to stabilize MMP9 expression in order to augment oncogenesis . Furthermore, the combined expression of MMP7 and MMP9 has been suggested to be a good marker for the degree of malignancy and for the presence of lymphatic metastasis in esophageal cancer .…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The most recent study indicated that MMP7 can not only cleave the extracellular matrix (ECM) to promote tumor invasion but also cleaves nucleolin to stabilize MMP9 expression in order to augment oncogenesis. 23 Furthermore, the combined expression of MMP7 and MMP9 has been suggested to be a good marker for the degree of malignancy and for the presence of lymphatic metastasis in esophageal cancer. 24 However, to the best of our knowledge, correlation of MMP7 and MMP9 expressions and their correlation with lymphatic metastasis have not been well established in cervical cancer up to now.…”
Section: Introductionmentioning
confidence: 99%
“…Such diverse and crucial functions of nucleolin indicate the importance of this protein for the functioning of the cell. At the same time, the level of nucleolin has been found to increase in actively proliferating cells (Hsu et al 2015), which is important both for the normal cells of the organism and for pathologically multiplying cells of malignant tumors. In recent years, a large number of articles have been devoted to the study of nucleolin in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large number of articles have been devoted to the study of nucleolin in tumor cells. It has been shown that during the development of various types of malignant tumors nucleolin interacts with EGFR, Ras and Sp1, and this interaction leads to active tumor growth [Hsu et al 2015;Hung et al 2014]. In addition, in some types of malignant tumors, extranuclear cytoplasmic nucleolin has been shown to correlate with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation